Green biosynthesis of silver nanoparticles (AgNPs) FROM Vitex negundo plant extract and its phytochemical screening and antimicrobial assessment next to pathogenic microbes - Sarita, Dogra; Mamta, Devi Sharma; Shabana, Tabassum; Puranjan, Mishra; Arvind Kumar, Bhatt; Prakash, Bhuyar (Slovak University of Agriculture, 2023)
In the present study, green synthesis of silver-nanoparticle (AgNPs) is demonstrated using plant extract of Vitex negundo. Plant extract through six different solvents, including petroleum ether, benzene, chloroform, acetone, methanol, and water, was prepared and further investigated for its antimicrobial and antifungal activities using different bacterial and fungal strains. The phytochemical analysis was performed, where saponins, tannins, steroids, flavonoids and glycosides were detected in acetone, chloroform and methanolic extract. Subsequent analysis of synthesized AgNPs through dynamic light scattering suggested that particle sizes were 10-300 nm in size. The study indicated that the chloroform, acetone, and methanol extracts of Vitex negundo showed good inhibitory activity against Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis based on the zone of inhibition. The antimicrobial activity of the synthesized AgNPs suggested that it can inhibit the growth of both gram +ve and gram -ve microorganisms. The MIC value of AgNPs of methanolic extract of V. negundo detected was 0.078 mg/mL, which was relatively lower than that of the MIC value of its crude extract (1.25mg/mL). The observed MIC values concluded that the synthesized AgNPs had better antimicrobial activity and could be necessary for various applications, including medicine, biology, and industry